O open banking no Brasil, Reino Unido e Singapura: uma análise da regulação das APIs sob a perspectiva do direito concorrencial regulatório - Glacus Bedeschi (2021)
The present study analyzes the open banking model in Brazil, especially the way in which the implementation of data sharing interfaces, the APIs, has been regulated. For this purpose, it was decided to establish, specifically regarding the norms related to APIs, a comparison between the open banking models in the United Kingdom, Singapore, and Brazil. The research problem consists in verifying whether the rules concerning open banking in the studied jurisdictions are related to regulatory competition law, a notion elaborated by Dunne to distinguish the set of procedural and substantive characteristics common to regulatory law, but that has been frequently assumed by antitrust law, when it is used as a substitute or alternative to sectorial regulation. The initial hypothesis is that regulatory intervention regarding APIs bears the characteristics attributed to regulatory competition law. To prove this hypothesis, the scenario of the banking market in the moments prior to the proposition of open banking are analyzed, as well as the factors that influenced the adoption of this intervention, the use of technology in this segment and how technological resources collaborate to the emergence of new business models. From this framework, the present study seeks to conceptualize open banking and present the regulators' justifications for its adoption, as well as examine the use of APIs as a technological foundation for the achievement of open banking and the consequences of this practice. After this analysis, the study concludes that the rules relating to open banking come closer, to a greater or lesser extent, to the theory of regulatory competition law, depending on the studied jurisdiction.